Infrastructure development in Kenderan Village, Tegallalang sub-district, Gianyar regency - Trisuci Arnawati Ida Ayu; Laksmini Ni Luh Putu; Natalia Wulansari Ni Ketut; I Wayan Runa; Putu Aryastana (Journal of Infrastructure Planning and Engineering, 2023)
Gianyar Regency has many villages that can be relied upon as tourist destinations due to their cultural and natural potential. Kenderan Village has a natural atmosphere with vast stretches of rice fields and hills, which are the main attractions of this village. Various potentials can be developed through ecotourism concepts as tourist attractions. The development of tourist village infrastructure involves the arrangement of the area and environment to maintain its natural state, as well as the optimal development of other supporting tourist facilities that have not been utilized. The aim of this research is to identify the potentials in Kenderan Village (cultural, natural, and village potentials) and to determine the necessary infrastructure for the development of Kenderan Village as a tourist village. This study uses observation, interviews, and documentation as research techniques, employing the SWOT approach. The results of this research show that there are various tourism potentials that can be developed into various attractions and activities, which can be categorized into three types: natural potentials (rice fields, plantations, and natural beauty), cultural potentials (archaeological sites, Beji Telaga Waja, and Pura Griya Sakti Manuaba), and village potentials (Puri Agung Kenderan and traditional settlements). The development of tourism potentials in Kenderan Village is expected to provide optimal benefits for the local community, entrepreneurs, and the government in a sustainable manner, while contributing to environmental preservation.